Factors Related To Hygiene Behavior Of Food Sanitation On Karak Crackers Manufacturing Workers In Home Industry In Karanganyar District, Indonesia - Dyah Suryani; Dhimas Iqbal Maulana; Suyitno (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2021)
Background: Foodborne disease is food poisoning that can cause illness or death as a result of consuming contaminated food. Food contamination can occur due to biological, physical, and chemical contamination, if food hygiene and sanitation behavior is not good in its application, especially for food handlers. Objectives: The purpose of this study was to determine the factors related to hygiene behavior of food sanitation in workers making karak crackers in the home industry of Kerjo Sub-district, Karanganyar Regency, Central Java Province, Indonesia. Research Method: This study was using the quantitative analytical observational method with a cross-sectional design. The number of samples was 38 workers making Karak crackers with a total sampling technique. Data analysis used fisher's exact CI 95% (α = 0.05). Findings: This study found that the majority of the age range was 17-45 with education level (81.6%), knowledge level (65.8%), negative attitude (52.6%), and poor food sanitation hygiene behavior (68.4%). The results of Fisher's exact test showed that the variables of age (p-value = 0.147) and education level (p-value = 0.176) were not significantly related to hygiene behavior of food sanitation. While the level of knowledge (p-value = 0.30) and attitudes (p-value = 0.49) have a significant relationship. Conclusion: In sum, the level of knowledge and attitudes of the respondents are the factors that influence the hygiene behavior of food sanitation. Therefore, it is necessary to conduct training on food hygiene and sanitation practices for food handlers.